(untitled) (Research, Society and Development, 2021)
In order to determine the possibility of increasing the planting window in the practice of direct sowing of paricá, the present work aims to determine the effect of the sowing depth on the quality of seedlings and in the establishment of the best planting window of Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby (Paricá), even in a period of low rainfall in the southeastern state of Pará. In the experiment, 6 treatments were defined according to the depth, being: surface depth (T1), 05 cm (T2), 10 cm (T3), 15 cm (T4), 20 cm (T5), and 30 cm (T6). Seedling emergence and survival at different depths were analyzed, and after 45 days, three variables were analyzed depending on the length of the seedlings (length of the depth at which the seed was placed to the end of the root, length from the depth of the seed to the neck, and neck length to the top of the seedling), thus seeking to evaluate the quality of seedlings produced, and to determine the best sowing depth that allows the increase of the planting window in unfavorable water conditions, the depth that showed the best results was the treatment of 10 cm, and was subsequently applied by direct sowing at this depth in commercial planting of paricá in the municipality of Abel Figueiredo in order to prove the experiment. The data from the first phase were analyzed by regression analysis considering two quantitative variables and adjusted equations for reliability testing. For the data of the second phase of the experiment, the percentage, mean and standard deviation of the survival and mortality data obtained in the four plots were calculated. The results obtained demonstrate great potential for expanding the planting window of the species, making new experiments necessary in order to prove the establishment of the paricá planting window.